Implementation Of Corporate Social Responsibility In Companies As A Form Of Empowerment Of Islamic Economic Production Principles - Wibowo, Suseno Adi; Prastika, Dian; Wahyu, Muhammad (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2021)
From an Islamic perspective, production activities in companies are based on the principles or values adopted by Islamic teachings which are sourced from the Al-Qur’an and As-Sunnah which aim to obtain benefits for human life. One of them is by applying the concept of corporate social responsibility as a form of concern in building the surrounding environment to improve the quality of life for a better and more prosperous. This study aims to identify and analyze the implementation of the concept of corporate social responsibility as a form of embodiment of the principles of production activities in companies according to an Islamic perspective. This study uses a normative juridical approach, which is focused on examining the application of norms or norms in positive law. The results of this study indicate that production activities in the perspective of Islamic economics are not only oriented to gain profit alone but to obtain the benefit of the individual (self-interest) and the benefit of society (social interest) in a balanced way. The manifestation of the principle of justice in production is the implementation of corporate social responsibility or known as Corporate Social Responsibility which is in line with Islamic teachings which teach balanced responsibility in all its forms and scopes. Keywords: Production, Economy, Corporate Social Responsibility.